7m+48=8(m+7)

Simple and best practice solution for 7m+48=8(m+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7m+48=8(m+7) equation:


Simplifying
7m + 48 = 8(m + 7)

Reorder the terms:
48 + 7m = 8(m + 7)

Reorder the terms:
48 + 7m = 8(7 + m)
48 + 7m = (7 * 8 + m * 8)
48 + 7m = (56 + 8m)

Solving
48 + 7m = 56 + 8m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8m' to each side of the equation.
48 + 7m + -8m = 56 + 8m + -8m

Combine like terms: 7m + -8m = -1m
48 + -1m = 56 + 8m + -8m

Combine like terms: 8m + -8m = 0
48 + -1m = 56 + 0
48 + -1m = 56

Add '-48' to each side of the equation.
48 + -48 + -1m = 56 + -48

Combine like terms: 48 + -48 = 0
0 + -1m = 56 + -48
-1m = 56 + -48

Combine like terms: 56 + -48 = 8
-1m = 8

Divide each side by '-1'.
m = -8

Simplifying
m = -8

See similar equations:

| 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 | | (r-p)/(x-q)=m | | -5x-(-3*-13)=30 | | 2x-4-6=0 | | 12+[6+(13-7)]2-5= | | 72/4.8=20.4/c | | -(x-8)+4=2(-1)+x | | y+4.3=5.9 | | 42x^2-40x+8=0 | | 5k^2+35k+60=0 | | -(x-8)+4=2(1.25)+x | | 12/x=7/3 | | -(x-8)+4=2(0)+x | | 3(2p+7)=1 | | 7/n=24.5/56 | | 7(1-5r)+6r=94 | | 6(9x+2)=54x-7 | | X/9=7/5 | | -(x-8)+4=2(-5.7)+x | | a(ax-a)+6(x+6)=0 | | x^2-5y^2-4x+4y-6=-6y^2-6y+10x-64 | | 84/x=8 | | 5y^2=11y^2 | | -2a+b=c | | 7(2p+3)=12 | | 6x-80=4x-100 | | 9x-7w+4x+7y+2y+3w= | | 3.25/2.5 |

Equations solver categories